An Analysis of Speech Act in Wish Movie - Fitria Salsabila (INDO PUBLISHING, 2025)
This study aims to analyze the speech acts in the dialogue of the film Wish, focusing on identifying the types of speech acts and the functions and intentions behind them. This study is based on the importance of understanding the strategic use of language in film dialogue as a reflection of social interaction and complex emotional expression. This study employs a descriptive qualitative approach, collecting data through the transcription and analysis of film dialogue using John Searle's speech act theory. The expected results are the classification of speech act types, such as assertive, directive, expressive, commissive, and declarative. Additionally, there will be an in-depth understanding of how these speech acts construct meaning, influence interactions between characters, and reinforce themes and messages in films. The research data consisted of 69 utterances taken from the film's dialogue transcripts and analyzed qualitatively and descriptively using a pragmatic approach. The results showed that assertive speech acts dominated, with 35 sentences, followed by directive speech acts with 17 sentences, expressive speech acts with 12 sentences, and commissive speech acts with 5 sentences. No declarative speech acts were found. Assertive speech acts primarily occur in situations involving conflict or leadership. They function as invitations and commands that motivate collective action. This analysis links speech act function to dialogue context, enriching our understanding of how language builds power, expresses emotion, and conveys social meaning in film narratives. The study provides pragmatic insights that can inform further research in film discourse analysis and language teaching.